QUANDO HISTÓRIA E JORNALISMO SE ENCONTRAM: os enunciados jornalísticos de Veja como dispositivos de poder (2011 – 2016) - Silva, André Luís Andrade (2019)
The present work aims at weaving discussions about the journalistic practice of Veja magazine. To do this, the editions published between 2011 and 2016 will be used as a corpus of research, which will be examined by the genealogical analysis of Michel Foucault, having as a guiding thread warns of the possible effects of know and the identification of the forms of exercise of power. The main objective of this work is to investigate how Veja discourses influence readers' perception of reality. That is, how, through journalistic discourse, this journal seeks to subjectify its reading public, to conduct behaviors, perpetuating pre-established stereotypes and concepts in our society. The analysis assumes that the magazine is a biopolitical device, which calls its readers to participate and be satisfied in the world by creating cognitive maps that show the way to success. Summons seek in their readers, modulations and conforming behaviors, in order to manage their lives and lead their choices. The first chapter focuses on the editorial Letter to the Reader and concerns start with how the order of discourse is composed in this space, how its production becomes possible through the selection, control, distribution, silencing, exclusion and limitation of the discourses speeches. In other words, the objectives are to show which desire truths Veja it seeks to legitimize through its discourses, as the journal builds credibility with its readers so that they take their statements as true. In the second chapter, the analyzes are directed to the interview space. The Yellow Pages diagnosis is made from a gender perspective, as men and women are not invited to talk about the same themes. The women talk about the private space, the men talk about the public space, contributing and enabling a will of truth favorable to Dilma Rousseff impeachment. In the third chapter, we turn to the covers of Veja. The objective is to discuss how the magazine seeks to legitimize this space as a place of authority, in which, through articulations between texts and images, it seeks to build identity groups responsible for producing a polarization in the brazilian political sphere, the construction of a We as opposition to a Them. The research in Veja consists in to question the naturalized gaze on this communication vehicle, allowing us to identify the knowledge and forces that cross our present time.